'Caries disease among an elderly population—A 10‐year longitudinal study'. Issue 2 (21st February 2021) - Edman, Kristina; Holmlund, Anders; Norderyd, Ola
Abstract: Objectives: To investigate the prevalence of dental caries and to identify risk factors for dental caries in an elderly population between 2008 and 2018. Methods: This longitudinal study used data from a questionnaire survey and a clinical examination administered on two occasions 10 years apart to 273 individuals who were 65 and 75 years of age in 2008. The variables included were prevalence of dental caries as well as socioeconomic and socio‐behavioural factors. Results: The number of teeth decreased in both age groups by a mean of 2 over the 10‐year study period, but the prevalence of dental caries remained stable. Approximately, a quarter of the participants had caries lesions. Toothbrushing once a day or less was the factor most strongly correlated with dental caries lesions (OR: 3.82, 95% CI: 1.68–8.66, p = 0.001), followed by need for homecare (OR: 3.50, 95% CI: 1.55–7.93, p = 0.003) and interproximal cleaning less than once a day (OR: 2.65, 95% CI: 1.36–5.19, p = 0.004). Conclusions: This longitudinal study revealed no increase in the prevalence of dental caries lesions, indicating that good oral health can be preserved among elderly people. The highest risk for dental caries lesions was among participants with inadequate oral hygiene routines (toothbrushing once a day or less and seldom using interproximal devices) and in need of help in daily living, emphasizing the importance of oral hygiene and collaboration between dental services and community‐based health care.